Software libero per lo sviluppo in Africa orientale - Mandrici, Andrea; Carugati, Caterina; Leonardi, Matteo (GEOmedia, 2010)
Free Software for development in East Africa Since 1999 Istituto Oikos (Italian NGO) in partnership with Oikos East Africa (Tanzanian NGO) are carrying out integrated development projects in collaboration with local Government Authorities at Regional, District, and Village level. With the aim to ensure sustainability to the interventions addressed to strengthen the governance capacities and the use of IT technologies in the rural areas, the projects have promoted the use of Free Software tools such as Ubuntu and Debian Linux as OS; Qgis and GRASS as G.I.S.; SQLite/Spatialite and PostgreSQL/PostGIS as Spatial-enabled DBRMS, OpenOffice as productivity suite.